Stories from the Heart: Narratives of Change in Therapeutic Enactment - Black, Timothy G. (Canadian Journal of Counselling and Psychotherapy, 2009)
Research was conducted on the experience of change for participants in a group-based psychotherapy approach called Therapeutic Enactment (TE), which involves the enactment of embodied narratives of participants’ past experiences. This study asked the question, “What is your story of change in TE?” The author conducted in-depth interviews with five TE protagonists, asking each person to tell their story of change in therapeutic enactment. The current article provides excerpts from each participant’s narrative, highlighting the changes that clients attributed to their TE experience. Suggestions for counsellors considering TE for themselves or their clients and future research directions are discussed.